The Effect of Peer Feedback Technique on Students' Writing Achievement at Eleventh Grade Students in SMA Negeri 1 Kubutambahan - ., Ni Ketut Arie Suasti Wahyuni; ., Dra. Luh Putu Artini, MA., Ph.D.; ., Kadek Sonia Piscayanti, S.Pd., M.Pd. (Universitas Pendidikan Ganesha, 2017)
THE EFFECT OF PEER FEEDBACK TECHNIQUE ON STUDENTS' WRITING ACHIEVEMENT AT ELEVENTH GRADE STUDENTS IN SMA NEGERI 1 KUBUTAMBAHAN By I Ketut Arie Suasti Wahyuni, Nim 1312021236 English Education Department Ganesha University of Education ABSTRACT The aim of this research was to find out the effect of Peer Feedback technique toward students’ writing achievement of Eleventh grade students in SMA Negeri 1 Kubutambahan. This study was a quasi-experimental research which used post-test only control group design. The population of this study was 178 students from eleventh grade of SMA Negeri 1 Kubutambahan. The samples of this study were 34 students of XI MIPA2 and 32 students of XI MIPA3 of eleventh grade in SMA Negeri 1 Kubutambahan selected by administering cluster ramdom sampling technique. The data were analyzed quantitatively by using descriptive and inferential statistics analysis. It was found that the mean score of the experimental group was 85.62 while the mean score of the control group was 82.48. It means that the experimental group was better than the control group in term of their writing achievement. Additionally, the value of t-obs (sig.(3-tailed)) was 0.0001. Since the value of sig.(2-tailed) was less than 0.0 (p